2021
DOI: 10.1182/blood.2020007075
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 mutation contributes to myeloid dysplasia in mice by disturbing heme biosynthesis and erythropoiesis

Abstract: Isocitrate dehydrogenase (IDH) mutations are common genetic alterations in myeloid disorders, including acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). Epigenetic changes, including abnormal histone and DNA methylation, have been implicated in the pathogenic build-up of hematopoietic progenitors, but it is still unclear whether and how IDH mutations themselves affect hematopoiesis. Here, we show that IDH1-mutant mice develop myeloid dysplasia in that these animals exhibit anemia, ineffective e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Expression of these mutations in mouse models initiate hematologic malignancy characterized by an increase in early hematopoietic progenitors, splenomegaly, anemia, hypermethylated histones, and altered DNA methylation patterns similar to those found in patients with AML with IDH1/2 mutations. It has been also shown that IDH1 mutant mice develop myeloid dysplasia via disturbance of heme biosynthesis and erythropoiesis, thus highlighting the essential role of IDH1 in normal erythropoiesis ( 116 ). Overexpression of mutant IDH enzymes can induce histone and DNA hypermethylation, as well as block cellular differentiation, which can be reversed by small molecule inhibition of the mutant enzymes ( 117 119 ).…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…Expression of these mutations in mouse models initiate hematologic malignancy characterized by an increase in early hematopoietic progenitors, splenomegaly, anemia, hypermethylated histones, and altered DNA methylation patterns similar to those found in patients with AML with IDH1/2 mutations. It has been also shown that IDH1 mutant mice develop myeloid dysplasia via disturbance of heme biosynthesis and erythropoiesis, thus highlighting the essential role of IDH1 in normal erythropoiesis ( 116 ). Overexpression of mutant IDH enzymes can induce histone and DNA hypermethylation, as well as block cellular differentiation, which can be reversed by small molecule inhibition of the mutant enzymes ( 117 119 ).…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…DNA and histone hypermethylation is a feature that is observed across most investigated types of cancer that frequently contain IDH1/2mt, such as glioma, 40 chondrosarcoma, 41,42 cholangiocarcinoma, 20 and AML. 16 Furthermore, genomic hypermethylation and an associated block of differentiation are induced by the expression of mtIDH1/2 or the administration of D-2-HG in cell models related to these types of cancer, such as primary human astrocytes, 43,44 human and mouse neural stem cells, [45][46][47] human and mouse mesenchymal stem cells, 42,48 mouse hepatoblasts, 49 and mouse hematopoietic cells, 16,50,51 but also human embryonic cells and mouse adipocytes. 52 These findings were associated with an increased number of IDH1/2mt cancerous stem cells when these mutations were induced in benign stem or progenitor cells of these tissues.…”
Section: Epigenetic Hypermethylation and Cellular Dedifferentiation In Mtidh1/2 Cellsmentioning
confidence: 99%
“…The resulting succinyl-CoA deficiency attenuates heme biosynthesis in IDH1mt hematopoietic cells, blocking erythroid differentiation at the late erythroblast stage and the erythroid commitment of hematopoietic stem cells. 51…”
Section: Epigenetic Hypermethylation and Cellular Dedifferentiation In Mtidh1/2 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is particularly prominent in IDH1 -mutated MDS and AML, where the defective IDH1 enzyme results in a very high accumulation of 2-HG rather than α-KG [ 38 ]. Recently, published data in mice have shown that 2-HG inhibits oxoglutarate dehydrogenase activity and reduces succinyl-CoA production, which leads to attenuation of heme biosynthesis and ineffective erythropoiesis [ 39 ].…”
Section: Metabolic Changes In the Hspc Poolmentioning
confidence: 99%